Palladium(ii) complexes with electron-poor, 4, 5-disubstituted diimidazol-2-ylidene ligands: synthesis, characterization and catalytic activity1. Issue 20 (28th May 2015) - Pinter, Piermaria; Biffis, Andrea; Tubaro, Cristina; Tenne, Mario; Kaliner, Maria; Strassner, Thomas
<x xml:space="preserve">Abstract</x> Palladium(ii) complexes with N-heterocyclic dicarbene ligands featuring electron-withdrawing substituents have been prepared and tested as catalysts in alkyne hydroarylations.